Excessive, flexible and (still) seen as gender neutral Journalists' perceptions about their job during the Covid-19 pandemic - Alcantara, Juliana (2024)
Mainstream newsroom routines have faced significant shifts in the last decades. Regardless of its nature, these changes can be seen from a gender perspective and framed within neoliberalism, seen as a structural force affecting people’s lives and an ideology of governance that shapes subjectivities. In this paper, we aim to discuss how neoliberalism influenced the implications of the Covid-19 pandemic on newsrooms and journalists’ working conditions from a gender lens. For this purpose, thirty semi-structured in-depth interviews were conducted between October and December 2021 with Portuguese female and male junior and senior journalists of different levels of hierarchy working in mainstream media. Their perceptions of the pandemic impact on news production show the intersections of sexism and neoliberalism in the newsroom settings. Journalists accept as part of the job the long working hours and the personal cost of health protection material and essential equipment to work from home while normalising the work-home conflict as a private woman’s matter. These findings are discussed as reflecting how neoliberal logic has made the impacts of the pandemic heavier, especially for women.